High performance full diversity LDPC codes construction and performance analysis for H-ARQ channels - Rui GUO; Fang-ning HU; Ji-lin LIU (Tongxin xuebao)
In order to improve the performance of communication system with hybrid automatic repeat request(H-ARQ),a kind of full diversity low density parity check(LDPC)codes on H-ARQ block-fading channels was proposed.First,the outage probability and inherent diversity were analyzed,then a kind of full diversity PDPC codes for H-ARQ channel was designed.The new proposed LDPC codes connected the initial transmission with the repeated transmissions by root-connection to get extern diversity gain.In addition,the relationship between the structure of full diversity LDPC codes and the coding gain was given,and an algorithm to improve coding gain was brought forward by increasing the proportion of full diversity parity bits.Simulation results show that the proposed algorithm can not only achieve full diversity,but also get better performance than constructed LDPC codes at present.